Wind Turbines and Property Values: A Meta-Regression Analysis - Marvin Schütt (Environmental and Resource Economics, 2023)
A key concern for property owners about the set up of proximate wind turbines is the potential devaluation of their property. However, there is no consensus in the empirical hedonic literature estimating this price-distance relationship. It remains unclear if the proximity to wind turbines reduces, increases, or has no significant effect on property values. This article addresses this ambiguity, combining 720 estimates from 25 hedonic pricing studies in a first comprehensive meta-analysis on this topic. Using Bayesian model averaging techniques and novel publication bias correction methods, I calculate an average of the reported estimates that is free from misspecification and publication bias. In economic terms, I find an average reduction in property values of -0.68%for properties 1.89 miles away, which turns to zero beyond 2.8 miles. Next to publication selection, the studies' ability to control for confounding factors such as pre-existing price differentials and spatial effects explains the variance in reported effect sizes.
Keywords: 330; Meta-analysis; Wind turbines; Property values; Hedonic pricing; Publication bias; Bayesian model averaging